Lexical foes one more time - Gabrovšek, Dušan (Mostovi (Ljubljana), 2002)
The article (invited contribution) is based primarily on the author's work done in the period 1990-95. It provides a fairly detailed discussion of the various possibilities in interpreting and analyzing the interlingual concept of false friends on teh lexical level, focusing on certain rarely discussed wider aspects of the topic (e.g. vague awareness of the meaning of L1 item, L2item causing lexical error in L1, double-difficulty-type false friendship, decoding vs. encoding, word-family-related problems, proper names). It also summarizes some lexicogarphical observations relating to dictionary treatment of the topic. The references represent a selection of pertinent recent writings on the subject published for the most part outside Slovenia.
Keywords: dvojezični slovarji; lažni prijatelji; leksikografija; paronimi